ANALISIS USAHA KECIL MENENGAH PENGOLAHAN MINYAK KELAPA RAKYAT DI KECAMATAN ENOK - Junianto, Riky; Hadi, Syaiful; Muwardi, Didi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was to determine the development of Small and Medium Enterprises (SMEs) and know the cost, revenue, efficiency, and the turning point of SME capital coconut oil processing in District Enok. Determination of the sample area was randomly (random sampling) with consideration District of Enok is an area that is still a lot of oil processing SMEs than that seen from the trenches conditions of transport and farm roads were damaged and neglected. The number of respondents for SMEs oil processing as much as 12 businessmen. The data used are primary data and secondary data. Data was collected through observation, interviews and recording. These results indicate that during the period 2010-2014 the number of SMEs in the district of palm oil processing Enok continued to decline with total growth declined by -20.67% per year, the average total cost incurred by employers oil processing are sold in the District of Enok by Rp.87.503,25, while efforts for household consumption of Rp.24.438,89. The average profit earned coconut oil entrepreneur who sold for Rp.71.712,25, coconut oil sold for consumption if the average profit of Rp.-1909.67. RCR oil processing SMEs that sold an average of 1.80, which means coconut oil processing business is profitable and feasible to be developed, while RCR SMEs oil processing for the needs of an average household of 0.90 which means that the coconut oil processing SMEs loss and does not deserve to bedeveloped. The turning point capital coconut oil processing business sold already profitable, while the turning point coconut oil processing business capital for household consumption losses. Keywords: Small and Medium Enterprises, Coconut Oil.Â